2021
DOI: 10.1101/2021.10.23.465573
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A focal adhesion kinase-YAP signaling axis drives drug tolerant persister cells and residual disease in lung cancer

Abstract: Targeted therapy is effective in many tumor types including lung cancer, the leading cause of cancer mortality. Paradigm defining examples are targeted therapies directed against non-small cell lung cancer (NSCLC) subtypes with oncogenic alterations in EGFR, ALK and KRAS. The success of targeted therapy is limited by drug-tolerant tumor cells which withstand and adapt to treatment and comprise the residual disease state that is typical during treatment with clinical targeted therapies. Here, we integrate studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 61 publications
(99 reference statements)
0
15
0
Order By: Relevance
“…This is supported by studies implicating YAP activation in persister cells after EGFR TKI treatment 44 . We recently reported YAP-driven transcriptional adaptation as a functional mechanism of TKI drug tolerance 45 . In this study, we found in experiments in humanized mice that YAP reduced treatment sensitivity to osimertinib and enhanced an immunosuppressive tumor microenvironment supporting tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by studies implicating YAP activation in persister cells after EGFR TKI treatment 44 . We recently reported YAP-driven transcriptional adaptation as a functional mechanism of TKI drug tolerance 45 . In this study, we found in experiments in humanized mice that YAP reduced treatment sensitivity to osimertinib and enhanced an immunosuppressive tumor microenvironment supporting tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, RNA-seq analyses from an EGFR L858R -harbouring PDX model of lung adenocarcinoma 38 treated with the EGFR inhibitor erlotinib (Extended Data Fig. 12f) or the EGFR inhibitor osimertinib 29 (Extended Data Fig. 12g) also revealed an increase in A3B mRNA levels and a trend towards decrease in UNG mRNA levels upon treatment.…”
Section: Main Textmentioning
confidence: 98%
“…10a). To confirm these transcriptional changes, an independent RNA-seq dataset was examined 29 , generated from EGFR-mutant PC9 cells treated with the EGFR TKI osimertinib for 9 days. These EGFR TKI-treated cells also displayed a significant upregulation of A3B and downregulation of UNG transcripts (Extended Data Fig.…”
Section: Main Textmentioning
confidence: 99%
“…VT2 and other TEAD palmitoylation inhibitors have shown efficacy in blocking resistance development when used in combination with osimertinib in mouse models of non-small cell lung cancer. 76 , 77 …”
Section: Discussionmentioning
confidence: 99%